Application of 4-chloro-7-nitrobenzofurazan for the analysis of propafenone and diltiazem hydrochlorides using kinetic spectrophotometric and spectrofluorimetric methods - Ayad, Magda Mohamed; Abdellatef, Hisham Ezzat; Hosny, Mervat Mohamed; Sharaf, Yassmin Ahmed (European Journal of Chemistry, 2013)
Several simple, sensitive, accurate and inexpensive spectrophotometric and spectrofluorimetric methods were developed for the determination of propafenone HCl and diltiazem HCl using 4-chloro-7-nitrobenzofurazan (NBD-Cl) accompanied with kinetic study, either in pure form or in pharmaceutical preparations. In this work, the cited drugs react with (NBD-Cl) in presence of borate buffer of pH = 7.6 at a fixed time of 30 minutes on thermostated water bath at (75-80 °C). The absorbance was measured using spectrophotometric technique at 489 and 481 nm for propafenone HCl and diltiazem HCl, respectively, or by using spectrofluorimetric technique after dilution at the specific wavelength of excitation and emission.The calibration curves were linear in the range of 4-44, 16-96 µg/mL when using spectrophotometric method, and 0.4-3.6, 1.6-8.8 µg/mL when spectrofluorimetric method was applied for propafenone HCl and diltiazem HCl, respectively. The limit of quantitation and the limit of detection were also calculated. The methods were applied successfully to commercial dosage form and can be further applied for their determination on a large scale in quality control laboratories. The obtained results statistically agreed with those obtained by reference methods. The determination of the studied drugs by the fixed concentration and rate constant methods is feasible with the calibration equations obtained, but the fixed time method proves to be more applicable.